2011
DOI: 10.1177/0969733010386162
|View full text |Cite
|
Sign up to set email alerts
|

Being a good nurse and doing the right thing: A replication study

Abstract: This qualitative research study, a replication of a study published in 2002, investigated the qualities of a good nurse and the role ethics plays in decision making. After reviewing the limitations of the published work, the current study implemented modifications related to the research questions, sample selection, data collection, and use of software for data analysis. The original study identified seven categories that related to being a good nurse and doing the right thing. In the present study, the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 12 publications
2
35
1
2
Order By: Relevance
“…Respect in interpersonal relationships, and support for each other is necessary in nursing and contributes to the health of patients. These findings coincide with others (Catlett, Lovan, 2011;Cleary et al, 2014;Päätalo, Kyngäs, 2016) that suggest a positive emotional atmosphere in nursing depends on nurse-nurse interactions. Students experienced the hierarchical interrelationships within nursing, whereby nurses are seen as superior to patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Respect in interpersonal relationships, and support for each other is necessary in nursing and contributes to the health of patients. These findings coincide with others (Catlett, Lovan, 2011;Cleary et al, 2014;Päätalo, Kyngäs, 2016) that suggest a positive emotional atmosphere in nursing depends on nurse-nurse interactions. Students experienced the hierarchical interrelationships within nursing, whereby nurses are seen as superior to patients.…”
Section: Discussionsupporting
confidence: 80%
“…Empathy and understanding regarding patients and relatives are essential features of good nurses, in order to ensure the quality of care, and to reduce patients' suffering. Empathy is interrelated with compassion, and is a typical feature of good nurses (Catlett, Lovan, 2011). Our research revealed that empathy may be emotionally painful for nurses.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this section, I briefly discuss the relevance of virtues to professional education, personnel recruitment and selection, and performance appraisal. make the yet stronger claim that virtues relevant to nursing should be a requirement for admission of candidates to schools of nursing (Catlett and Lovan 2011). The main reason for this is that patients' dissatisfaction with nursing care has been shown to be partly due to nurses' poor traits of character (Chen and Hsu 2015), and it is hoped that character formation will improve the situation.…”
Section: The Relevance Of Virtues In Professional Lifementioning
confidence: 99%